The Interaction Pattern between a Homology Model of 40S Ribosomal S9 Protein of Rhizoctonia solani and 1-Hydroxyphenaize by Docking Study. (22nd April 2014) - Dharni, Seema; Sanchita,; Samad, Abdul; Sharma, Ashok; Patra, Dharani Dhar
Abstract : 1-Hydroxyphenazine (1-OH-PHZ), a natural product from Pseudomonas aeruginosa strain SD12, was earlier reported to have potent antifungal activity against Rhizoctonia solani . In the present work, the antifungal activity of 1-OH-PHZ on 40S ribosomal S9 protein was validated by molecular docking approach. 1-OH-PHZ showed interaction with two polar contacts with residues, Arg69 and Phe19, which inhibits the synthesis of fungal protein. Our study reveals that 1-OH-PHZ can be a potent inhibitor of 40S ribosomal S9 protein of R. solani that may be a promising approach for the management of fungal diseases.